Long-Term Acoustic Monitoring Reveals Site Fidelity, Reproductive Migrations, and Sex Specific Differences in Habitat Use and Migratory Timing in a Large Coastal Shark (Negaprion acutidens) - Pillans, Richard D.; Rochester, Wayne; Babcock, Russell C.; Thomson, Damian P.; Haywood, Michael D. E.; Vanderklift, Mathew A. (Frontiers in Marine Science, 2021)
Knowledge of the movement patterns of the lemon shark Negaprion acutidens is poor in contrast to the allopatric N. brevirostis. Using acoustic telemetry, we investigated daily (diel and tidal) and seasonal patterns in residency, fidelity, home range, habitat preference, and migratory patterns along the Ningaloo coast, Australia. Thirty eight adult N. acutidens were monitored for up 6.1 years (mean 2.5 y) with 19 animals detected for more than 3 years and 5 for more than 5 y. Approximately 50% of the tagged animals remained within 10 km of their tagging location for more than 12 months (average core home range of 1.7 km2). Surprisingly, residency of adults was greater than juveniles in this known nursery area. Adults showed a strong preference for lagoon habitats and moved into shallow nearshore habitats at high tide and at night. During winter months, female sharks shifted their core home range 0.45 km further offshore into deeper lagoon areas, a shift which is likely due to behavioral thermoregulation. Space use by males and females within core areas was asynchronous indicating sexual segregation by resident sharks. Both resident and non-resident sharks were detected up to 140 km away. These highly directional (southerly) and rapid movements (140 km in 2 days) were largely correlated with the parturition and mating periods with males departing 1–2 months earlier than females. In females, periodicity of migrations was variable with evidence of annual and biannual patterns. Negaprion acutidens are highly susceptible to over-fishing and movement data are essential to quantify spatio-temporal overlap with fisheries and assist with developing spatially explicit stock assessment models.